Thermomechanical Processing of Steels - María Rodríguez-Ibabe, José; Uranga, Pello (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book gathers a collection of papers summarizing some of the latest developments in the thermomechanical processing of steels. The replacement of conventional rolling plus post-rolling heat treatments by integrated controlled forming and cooling strategies implies important reductions in energy consumption, increases in productivity and more compact facilities in the steel industry. The metallurgical challenges that this integration implies, though, are relevant and impressive developments that have been achieved over the last 40 years. The frequency of the development of new steel grades and processing technologies devoted to thermomechanically processed products is increasing, and their implementation is being expended to higher value added products and applications. In addition to the metallurgical peculiarities and relationships between chemical composition, process and final properties, the relevance impact of advanced characterization techniques and innovative modelling strategies provides new tools to achieve the further deployment of the TMCP technologies. The contents of the book cover low carbon microalloyed grades, ferritic stainless steels and Fe-Al-Cr alloys, medium-Mn steels, and medium carbon grades. Authors of the chapters of this "Thermomechanical Processing of Steels" book represent some of the most relevant research groups from both the steel industry and academia.